Granulomatous pulmonary zygomycosis in a patient without underlying illness. Computed tomographic appearances and treatment by pneumonectomy. - Majid, A.A.; Yii, N.W. (1991)
Pulmonary zygomycosis rarely occurs in the absence of underlying disease. We report a patient with granulomatous pulmonary zygomycosis without underlying disease who presented with a pulmonary mass. We present the computed tomographic findings that we believe have not been described previously. We also report the successful treatment by pneumonectomy.